Isolation and characterization of a high-efficiency algicidal bacterium Pseudoalteromonas sp. LD-B6 against the harmful dinoflagellate Noctiluca scintillans - Wang, Junyue; Yin, Xueyao; Xu, Mingyang; Chen, Yifan; Ji, Nanjing; Gu, Haifeng; Cai, Yuefeng; Shen, Xin (Frontiers in Microbiology, 2022)
The dinoflagellate Noctiluca scintillans is a harmful algal species that is globally distributed and poses a certain threat to marine ecosystems. Recent research has shown that the application of algicidal bacteria is a promising method to prevent and control such harmful algal blooms, given its advantages of safety and efficiency. In this study, a strain of algicidal bacterium LD-B6 with high efficiency against N. scintillans was isolated from the coastal waters of Lianyungang, China. 16S rDNA sequence analysis showed that the strain LD-B6 belongs to the genus Pseudoalteromonas. Furthermore, the algicidal effect of LD-B6 on N. scintillans was investigated. The results showed that strain LD-B6 exerted strong algicidal activity against N. scintillans. After 12 h of bacterial culture addition to algal cultures at a 2% final volume rate, the algicidal rate reached 90.5%, and the algicidal activity of LD-B6 was influenced by the density of N. scintillans. In addition, the algicidal bacterium LD-B6 was found to indirectly lyse algal cells by secreting extracellular compounds. These algicidal compounds were stable, indicating that they are not proteins. Importantly, strain LD-B6 was broadly general, showing varying degrees of lysing effects against five of the six algal species tested. In summary, the isolated bacterial strain LD-B6 shows the potent algicidal capability to serve as a candidate algicidal bacterium against N. scintillans blooms.